Exploring Faculty and Student Frameworks for Engineering Knowledge Using an Online Card Sorting Platform - Chen, Diana A.; Hoople, Gordon D.; Ledwith, Nico; Burlingame, Eric; Bush, Seth D.; Scott, Gregory E. (International Journal of Engineering Pedagogy (iJEP), 2020)
In this study we investigate how faculty and students think about engineering us-ing a technique new to engineering education: card sorting. In card sorting partic-ipants sort stimuli (cards) into groups, in the process revealing how they catego-rize information. Here we examine how both engineering faculty (n=23) and first-year undergraduate students (n=62) categorize engineering scenarios. We found engineering faculty sort based on cross-disciplinary engineering activities rather than engineering disciplines. This is a surprising result as our educational frameworks are based around disciplines, and yet they are not the primary way in which faculty think. First-year students, on the other hand, showed little consen-sus on how to sort the scenarios. As a part of this paper we unveil an online card sorting platform Collection and Analysis of Research Data for Sorting (CARDS). CARDS allows researchers to create card sorting tasks, distribute them to participants for remote data collection, and analyze quantitative results.